Endoscopic Bulking Materials for the Treatment of Vesicoureteral Reflux: A Review of Our 20 Years of Experience and Review of the Literature - Chertin, Boris (Hindawi Publishing Corporation, 2011)
Purpose. We reviewed our 20 years of experience and the current literature regarding the long-term outcome of endoscopic treatment of vesicoureteric reflux (VUR) using the different tissue bulking substances with a special emphasis on the long-term efficacy. Material and Methods. Our own experience and the current literature on the long-term results after endoscopic treatment using various bulking agents were reviewed. Results. Short-term data following endoscopic treatment of VUR is similar to the various substances and comparable in the majority of the series to the success rate following open surgery. Recently, a relatively high recurrence rate was noticed especially with the use of dextranomer hyaluronic acid (Dx/HA) as a tissue augmenting material which raises the need for further search for alternative substances. Conclusions. Unfortunately, there is a significant shortage of evidence-based literature on the long-term followup after endoscopic correction of reflux with various substances. No doubt, there is a high recurrence rate during long-term followup after Dx/HA injection, and there is probably lack of proper evaluation regarding the long-term efficacy of other bulking materials. These facts demand long-term close observation and long-term studies beyond the routine protocols following endoscopic treatment of VUR and the correct parental counseling upon the endoscopic correction.